Noise-induced Cochlear Synaptopathy with and Without Sensory Cell Loss. (10th February 2020) - Fernandez, Katharine A.; Guo, Dan; Micucci, Steven; De Gruttola, Victor; Liberman, M. Charles; Kujawa, Sharon G.
Highlights: Loss of IHC synapses with cochlear neurons is ubiquitous after noise exposure. Synapse loss does not scale with TTS or PTS. Hair cell damage modifies synaptopathic outcomes. Threshold sensitivity measures dramatically underestimate noise risk. Abstract: Prior work has provided extensive documentation of threshold sensitivity and sensory hair cell losses after noise exposure. It is now clear, however, that cochlear synaptic loss precedes such losses, at least at low-moderate noise doses, silencing affected neurons. To address questions of whether, and how, cochlear synaptopathy and underlying mechanisms change as noise dose is varied, we assessed cochlear physiologic and histologic consequences of a range of exposures varied in duration from 15 min to 8 h and in level from 85 to 112 dB SPL. Exposures delivered to adult CBA/CaJ mice produced acute elevations in hair cell- and neural-based response thresholds ranging from trivial (∼5 dB) to large (∼50 dB), followed by varying degrees of recovery. Males appeared more noise vulnerable for some conditions of exposure. There was little to no inner hair cell (IHC) loss, but outer hair cell (OHC) loss could be substantial at highest frequencies for highest noise doses. Synapse loss was an early manifestation of noise injury and did not scale directly with either temporary or permanent threshold shift. With increasing noise dose, synapse loss grew to ∼50%, then declined for exposures yielding permanent hair cell injury/loss. All synaptopathic, but no non-synaptopathic exposures produced persistent neural response amplitude declines; those additionally yielding permanent OHC injury/loss also produced persistent reductions in OHC-based responses and exaggerated neural amplitude declines. Findings show that widespread cochlear synaptopathy can be present with and without noise-induced sensory cell loss and that differing patterns of cellular injury influence synaptopathic outcomes.